Development Teaching Basic SkillÃ¢â¬â¢s VCD Media to Improve Teaching Skills in Subjects Micro Teaching - Satutik Rahayu; Nur Lestari; I Gde Mertha (Department of Physics Education, Universitas Mataram, 2018)
This study aims to: 1) determine the quality of the results of VCDs that have been developed, 2) find out whether there is an increase in student teaching skills in micro-learning. This research is a development research using ADDIE (Analysis, Design, Development, Implementation and Evaluation) models. Validation of learning videos is done by learning media experts and user response questionnaires. Data analysis used descriptive analysis and N-Gain test. The results showed that the average score of the media expert validation was 86.7% in the good and usable category, while the results of the user response questionnaire were 87.9% in the good category and suitable for use. Hail the N-gain test found that there was an increase in the basic teaching skills of students after using the VCD of basic teaching skills in the micro-learning course which was 0.7.